BILATERAL GIANT ADRENAL MYELOLIPOMA - Tob, Noor Hafis Md; Tong, Chin Voon; Vergis, Melissa; Lee, Siow Ping (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Adrenal myelolipomas are rare, benign, non-functioning tumours consisting of mature adipose tissue and various hematopoietic components. They are typically small and asymptomatic and are, thus, diagnosed incidentally. We present a case of bilateral giant adrenal myelolipomas, including the results of biochemical laboratory tests and imaging studies. CASE A 45-year-old paraplegic female presented with increasing abdominal distention and pain. She has background diabetes and hypertension. On physical examination, she was normotensive, with a blood pressure of 133/80 mmHg. Abdominal examination revealed large, hard masses more prominent over the right side of the abdomen. Both lower limbs were erythematous and oedematous up to the midthigh. In the ward, she developed septic shock secondary to leg cellulitis complicated with acute kidney injury requiring haemodialysis. Contrast-enhanced computerized tomography (CECT) scans showed huge bilateral suprarenal masses with low Hounsfield units (HU): the right 191 x 246 x 344 mm while the left 100x145 x 119 mm. Initial hormonal workup showed non-suppressed cortisol levels on both overnight dexamethasone suppression tests (OnDST) (1086.3 nmol/L) and low-dose dexamethasone suppression tests (LDDST) (398.2 nmol/L). Plasma normetanephrine levels were high (2.8 nmol/L; normal <0.9). Repeated 24-hour urine metanephrines in the outpatient setting were normal. She underwent right adrenalectomy after a multidisciplinary discussion concluded a possibility of malignant transformation. Histopathological examination (HPE) showed Myelolipoma with a weight of 6600 g. Repeated OnDST post-surgery was normal. Giant adrenal myelolipomas can cause significant compression effects on surrounding structures and exhibit variable biochemical patterns. In this case, it produced false-positive results due to the presence of confounding factors. CONCLUSION This is a case of a bilateral giant myelolipoma with an initial false-positive functioning status biochemically and multiple sequelae. Nevertheless, appropriate hormonal workup is still essential prior to surgical intervention to avoid unnecessary catastrophic crises.